New Paradigm in Treating Cancer: Right on Target - Noorwati Sutandyo (Interna Publishing, 2016)
Cancer prevalence is increasing every year and now cancer is the third highest cause of death in developing countries. Effective anticancer treatment can prolong life and improve the patient's quality of life. Targeted therapy is a new therapeutic modality which targets specific molecules in the cancer cell and disrupts dysregulated signaling pathways involved in carcinogenesis. Since targeted therapy does not attack normal cells, its side effects are considered low compared to chemotherapy. More than 15 drugs have been approved for treatment in various human cancers. These drugs can largely be grouped into tyrosine kinase inhibitors and monoclonal antibodies. This review will focus on the most common agents within both groups.